Tracing the botanical origins of UK heather honey by relative quantification of plant DNA - Dodd, Sophie; Kevei, Zoltan; Karimi, Zahra; Kumar, Jane Jennifer Suresh; Koidis, Anastasios; Anastasiadi, Maria (Springer, 2025)
Heather honey is an important honey type produced in the UK, valued for its unique flavour, thixotropic texture and health-promoting properties. Botanical authentication can be challenging due to the natural variability in honey composition and typical pollen analysis relies heavily on expert knowledge. As an alternative, real-time PCR (qPCR) can be a rapid and robust method to identify floral species in honey. In this work, species-specific markers for Calluna vulgaris and Erica cinerea were developed and used to quantify 266 honey samples relative to the plant trnL P6 loop. The method classed 96% of 234 heather honeys as containing > 3% heather DNA, with 68% classified as dominant (> 45%) for ling heather origin. Moreover, high specificity was achieved with negligible amplification in the 32 non-heather honeys. Our qPCR method offered comparable results to melissopalynology, DNA metabarcoding, and digital PCR, showing potential as an alternative and accessible method for botanical authentication of heather honeys.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 40 Engineering; Complementary and Integrative Health; 3006 Food sciences; 4004 Chemical engineering